Host defences against Giardia lamblia. (August 2015) - Lopez‐Romero, G.; Quintero, J.; Astiazarán‐García, H.; Velazquez, C.
Summary Giardia spp. is a protozoan parasite that inhabits the upper small intestine of mammals and other species and is the aetiological agent of giardiasis. It has been demonstrated that nitric oxide, mast cells and dendritic cells are the first line of defence against Giardia. IL‐6 and IL‐17 play an important role during infection. Several cytokines possess overlapping functions in regulating innate and adaptive immune responses. IgA and CD4+ T cells are fundamental to the process of Giardia clearance. It has been suggested that CD4+ T cells play a double role during the anti‐Giardia immune response. First, they activate and stimulate the differentiation of B cells to generate Giardia‐specific antibodies. Second, they act through a B‐cell‐independent mechanism that is probably mediated by Th17 cells. Several Giardia proteins that stimulate humoral and cellular immune responses have been described. Variant surface proteins, α‐1 giardin, and cyst wall protein 2 can induce host protective responses to future Giardia challenges. The characterization and evaluation of the protective potential of the immunogenic proteins that are associated with Giardia will offer new insights into host–parasite interactions and may aid in the development of an effective vaccine against the parasite.